Melaka Historic City Council (MBMB) / Nur Adriana Muhammad Farhan - Muhammad Farhan, Nur Adriana (Faculty of Business and Management, 2023)
My practical journey which is very memorable and informative of 6 months of industrial training began here at Melaka Historic City Council (MBMB). This industrial training report will cover and provide the background of the company, my training experiences, the SWOT analysis of the company as well as the discussion and the recommendation that is suitable with the company. This report also includes all the experiences that I had throughout the industrial training session with the company such as problem-solving skills, communication skills, how to handle events, how to interact with other people and many more. Other than that, this report also will include the SWOT analysis of the company which will analyse the company's strengths, weaknesses, opportunities and threats that can be used for the company to come out with the best strategy. Some of the SWOT analysis of the company which are for strength are various types of services and the employee's attitude. Last but not least, this report also will provide some discussion and the recommendation for the company on how they can improve in order to be a better company that can give more benefits to the citizens at Malacca.